LEGAL RIGHTS OF CHILDREN BORN IN UNREGISTERED MARRIAGE - BRIEF OVERVIEW - Gelukashvili, Lili; Chiglashvili, Lia (European Scientific Journal, ESJ, 2014)
The main source for the family law is the constitution of Georgia. This is the supreme law of the country which acknowledges and identifies main authorities and freedom of a citizen; it also refers to the fundamental statues of the family – marriage relationship. Many foreign observers discuss such issues in relation to the accompanying social-economic problems that should not be left without attention. Among them the following ones should be outlined – decrease in marriage rates, cohabitation of couples in unregistered marriage, increasing birth rate of children born from unmarried couple, increase of unwed mothers, etc. Studying the rights of children born as a result of unregistered relationship provokes the greatest interest, because such children and their parents have been constantly expecting strict verdict from social communities for centuries. Statistic researches help us express our opinion that the children born as a result of unregistered marriage are mostly in need not only of material, but also of moral support what requires more attention from the side of the government as they are our citizens and the future of our country. Our purpose is to study these issues thoroughly, which have been painfully reflected on the future of children born from unmarried couples as well as on legal status of unwed parents.